Ethnic Differences of the Care Pathway Following an Out-of-Hospital Cardiac Event: A Systematic Review - Newport, Rochelle; Grey, Corina; Dicker, Bridget; Ameratunga, Shanthi; Harwood, Matire (Elsevier, 2023)
AIM: This systematic review aimed to determine to what extent and why the care pathways for acute cardiac events in the community might differ for minoritised ethnic populations compared to non-minoritised populations. It also sought to identify the barriers and enablers that could influence variations in access to care for minoritised populations. METHODS: A multi-database search was conducted for articles published between 1 January 2000 and 1 January 2023. A combination of MeSH terms and keywords was used. Inclusion criteria for papers were published in English, adult population, the primary health condition was an acute cardiac event, and the primary outcomes were disaggregated by ethnicity or race. A narrative review of extracted data was performed, and findings were reported according to the PRISMA 2020 guidelines. RESULTS: Of the 3552 articles identified using the search strategy, 40 were deemed eligible for the review. Studies identified a range of variables in the care pathway that differed by ethnicity or race. These could be grouped as time to care, transportation, event related-variables, EMS interactions and symptoms. A meta-analysis was not performed due to heterogeneity across the studies. CONCLUSION: The extent and reasons for differences in cardiac care pathways are considerable. There are several remediable barriers and enablers that require attention to achieve equitable access to care for minoritised populations.
Keywords: Emergency medical services; Out of Hospital Cardiac Arrest; Systematic review; Emergency medical services; Out of Hospital Cardiac Arrest; Systematic review; 4203 Health Services and Systems; 32 Biomedical and Clinical Sciences; 42 Health Sciences; Health Services; Clinical Research; Heart Disease; Cardiovascular; 8.1 Organisation and delivery of services; 8 Health and social care services research; Cardiovascular; 1103 Clinical Sciences; 1110 Nursing; 1117 Public Health and Health Services; Emergency & Critical Care Medicine; 3202 Clinical sciences; 4205 Nursing; 4206 Public health